High-Resolution Atom Interferometers with Suppressed Diffraction Phases - Estey, Brian (2015)
We experimentally and theoretically study the diffraction phase of large-momentum transfer beam splitters in atom interferometers based on Bragg diffraction. We null the diffraction phase and increase the sensitivity of the interferometer by combining Bragg diffraction with Bloch oscillations. We demonstrate agreement between experiment and theory, and a 1500-fold reduction of the diffraction phase, limited by measurement noise. In addition to reduced systematic effects, our interferometer has high contrast with up to 4.4×106 radians of phase difference, and a resolution in the fine structure constant of δα/α=0.25  ppb in 25 h of integration time.